Bilingualism and the Academic Achievement of First- and Second-Generation Asian Americans: Accommodation with Or without Assimilation? - Mouw, Ted; Xie, Yu (American Sociological Review, 1999)
Recent scholarship claims that bilingualism has a positive effect on the academic achievement of immigrant children. According to this perspective, growing up speaking two languages is beneficial because it stimulates cognitive development and allows immigrants a means of resisting unwanted assimilation. Immigrant children who are fluent bilinguals can use their native-language ability to maintain beneficial aspects of their ethnic culture while accommodating to the linguistic demands of an English-speaking society. Using data on first- and second-generation Asian American students from the 1988 National Educational Longitudinal Study, we test for these hypothesized effects of bilingualism. We find no evidence that bilingualism per se has a positive effect on achievement. Instead, speaking a native language with parents has a temporary positive effect if the parents are not proficient in English. These results indicate that the academic importance of bilingualism is transitional: The educational benefits of delaying linguistic assimilation exist only before immigrant parents achieve a moderate level of English-language proficiency.